Comparative analysis of immunosuppressive therapies for myelin oligodendrocyte glycoprotein antibody-associated optic neuritis: a cohort study. Issue 11 (30th April 2021) - Xie, Lindan; Zhou, Huanfen; Song, Honglu; Sun, Mingming; Yang, Mo; Lai, Ying Meng; Xu, Quangang; Wei, Shihui
Abstract : Aims: The optimal immunosuppressive therapy (IST) in patients with myelin oligodendrocyte glycoprotein antibody-associated optic neuritis (MOG-ON) remains uncertain. This study aimed to observe the disease course of MOG-ON and evaluate the therapeutic efficacy and tolerability of conventional immunosuppressants through Chinese cohort analysis. Methods: This bidirectional cohort study included 121 patients with MOG-ON between January 2015 and December 2018. The clinical features and annualised relapse rate (ARR) of patients with and without IST were analysed. Results: The median age at onset was 17.5 years, and the sex ratio (F:M) was 1.24. Of 121 patients, 77 patients relapsed and 61 patients were younger than 18 years at disease onset. The overall median ARR of 63 patients in the non-IST group was 0.5, with 46.0% patients showing relapse at a median follow-up of 33.5 months. In the IST group, the ARR decreased from 1.75 pre-IST to 0.00 post-IST in 53 patients who received IST exceeding 6 months, with 20.8% patients showing relapse at a median follow-up of 23.8 months. The relapse rates of patients treated with rituximab (RTX) and mycophenolate mofetil (MMF) were not statistically different, but the rate of discontinuation was significantly lower in the RTX-treated group (18.2% vs 57.7%, p=0.0017). Conclusion: This study provides Class III evidence that both MMF and RTX may lower disease activity in patients with MOG-ON, and RTX showed better tolerability than MMF. However, observation after a single attack remains a good option because less than half of patients not on treatment suffered a relapse.